Magento 2 and Elasticsearch Integration - Andy Sukanto Kan; Peter Boots; Bart Delvaux (Institute of Research and Community Outreach - Petra Christian University, 2020)
The purpose of this research is to extend the default integration of Elasticsearch in Magento 2.3 to search for other content which is category and content pages. The current search engine in Magento uses the default MySQL search engine, with the new update of Magento 2.3, Elasticsearch is introduced as an optional search engine. Elasticsearch provides a better and optimized full text search, however this new integration can only search the catalog products, therefore a way of extending the integration of Elasticsearch in Magento is searched for. The features that wanted to be implemented is Category search using Elasticsearch in Magento 2.